Nilai-nilai Budaya Jepang (Tinjauan Aspek Nilai Progresif dan Ekspresif Kebudayaan dalam Proses Modernisasi Jepang) - Sartini Sartini (Jurnal Filsafat "WISDOM", 1999)
The goal of developing country is to be a developed one. Country development is influenced by physical, social, and cultural condition. Vice versa, a progress of a country influences them Japan is a developed Asian country. The purpose of this research is to know some Japanese cultural values that support modernization and the impacts of the progress, and to reflect the reality.This research is a bibliograpical study. The material is books and written material about Japanese society. The research starts to look for the Japanese cultural values in progressive and expressive cultural balues. Then, looking at the negative impacts of the modern life will lead to make a reflective and evaluative thinking.The result of this research shows that first, Japanese progress is supported by character and cultural of the society such as hard working, discipline, saving, sincerity, loyality, group working, high dynamic appreciation for time, competitiveness. Second, creativity and productivity of the society can funfill the human need that being higher, but pleasure of life makes many bad impacts. Third, willing of the human being needs strong instution to decide the concept of progress around the country or the world. Progress of the civilization may be comprehended as long as a concept of enough, or as far as ratio of man can do.